EFFECT OF BENDING ANGLES ON THE GALVANIZING AND GALVANNEALING COATINGS ON THE STEEL PLATE COLD COMMERCIAL (SPCC) - Syahbuddin, Syahbuddin; Wiseno, Elbi; Sugiarto, Sugiarto (Jurnal Ilmiah Desain & Konstruksi, 2008)
This study conducted the effect of bending angles on the galvanizing and galvannealing coatingson the steel plate cold commercial. Both coatings consisted of serial Fe-Zn intermetallic layerssuch as -FeZn13, p-FeZn10, k-FeZn7 and -Fe3Zn10 layers with different fraction. The greaterpart of the first coating was the phase and in the other was the  phase. Formable of thecoatings was examined using bending test with angles about 150, 120, 90, 60 and 30 degrees. Asresults, the galvanizing coating except for bending angle of 30 degree seems strong for tensionload. By contrast, most galvannealing coatings bent in all angles were cracks runningperpendicular from the steel surface to -zinc region. Similar to the tension load, compressedload as resulted of the bending test did not provide any influence to the galvanizing coating, butsignificantly lead to cracks in the galvannealing coating both parallel and vertical direction tothe steel surface.